2021
DOI: 10.1002/adma.202100442
|View full text |Cite
|
Sign up to set email alerts
|

2D Electrolytes: Theory, Modeling, Synthesis, and Characterization

Abstract: A class of compounds sharing the properties of 2D materials and electrolytes, namely 2D electrolytes is described theoretically and demonstrated experimentally. 2D electrolytes dissociate in different solvents, such as water, and become electrically charged. The chemical and physical properties of these compounds can be controlled by external factors, such as pH, temperature, electric permittivity of the medium, and ionic concentration. 2D electrolytes, in analogy with polyelectrolytes, present reversible morp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 48 publications
1
13
0
Order By: Relevance
“…The typical images of scrolls [19,30] indeed suggest uniform interlayer separation consistent with our assumption. Equation (2) makes sense for scrolls as long as |φ 0 −φ 1 | ≥ 2π.…”
Section: Two-dimensional (2dsupporting
confidence: 88%
See 2 more Smart Citations
“…The typical images of scrolls [19,30] indeed suggest uniform interlayer separation consistent with our assumption. Equation (2) makes sense for scrolls as long as |φ 0 −φ 1 | ≥ 2π.…”
Section: Two-dimensional (2dsupporting
confidence: 88%
“…(Here, k B is the Boltzmann constant.) Similar analysis can be performed for graphene with alternative functionalizations [19].…”
Section: (B) the Differential Geometry Suggestsmentioning
confidence: 84%
See 1 more Smart Citation
“…It has been observed that nanocylinders and nano-cuboids of a higher aspect ratio represent more nanoparticle penetration inside the spheroid when plotting the normalized intensity against their normalized distance from the center is done. This comparison can be drawn more clearly by the two-photon microscopy highlighting the more accumulation of nanoparticles inside the spheroid for the higher aspect ratios of the nanocylinders and nano-cuboids sized drug molecules (Horacio et al, 2011; Lazzari et al, 2017 ; Costa et al, 2021 ). The higher aspect ratio, hence the larger surface area in contact, can be stated as one of the reasons for this favored penetration, which promotes a higher avidity between the cells and diffusion across spheroids.…”
Section: Kinetics Of Nanomedicine In Tumor Spheroidsmentioning
confidence: 99%
“…2D electrolytes have been previously defined in the literature as 2D materials that are functionalized with different chemical groups that experience either protonation or deprotonation in dispersion and become positively (2D cations) or negatively (2D anions) charged, respectively. [34] Our interest in 2D electrolytes is due to the following two considerations (Figure 1a): first, the aromatic domains in their basal plane can interact with the backbone of CPE-K via π-π stacking and hydrophobic interactions; second, they can be chemically functionalized with cationic groups to promote coulombic interactions. Chemically functionalized graphene oxide (GO) is employed as the model 2D electrolyte in this study.…”
Section: Conducting Polymer Hydrogels (Cphsmentioning
confidence: 99%